Smarter and more connected: Future intelligent transportation system - Agachai Sumalee; Hung Wai Ho (My University, 2018)
Emerging technologies toward a connected vehicle-infrastructure-pedestrian environment and big data have made it easier and cheaper to collect, store, analyze, use, and disseminate multi-source data. The connected environment also introduces new approaches to flexible control and management of transportation systems in real time to improve overall system performance. Given the benefits of a connected environment, it is crucial that we understand how the current intelligent transportation system could be adapted to the connected environment.
Keywords: Traffic Prediction and Management Techniques